DISCOVERY OF MAFIC GRANULITES FROM THE ALTAY OROGENIC BELT: EVIDENCE FROM MINERALOGICAL STUDY - Li Z.L.; Chen H.L.; Yang S.F.; Xiao W.J.; Tainosho Y. (My University, 2004)
The Altay mafic granulite (AMG). representing metamorphic product of granulite-facies in the lower crust, was first found in the Fuyun Wuqiagou, Altay progenic bell through detailed field survey and mineral-chemical study. The AMG consists of coarsegrained and fine-grained granulites with SiO_2 contents of 47.83%～53.57%, both of which have similar mineral assemblage of orthopyroxene, clinopyroxene, plagioclase, amphibole and brown biotite, Its mineral compositions of amphiboles and biotites are rich in Mg/(Mg+Fe~(2+)), probably having relationship with whole-rock chemistry of the rocks. Mineral chemistry addresses that orthopyroxenes have higher Mg/(Mg+Fe~(2+)) of 0.65-0.71, belonging to hypersthene, and having higher MgO+FeO contents, and lower Al_2O_3 contents and Ca/(Ca+Fe~(2+)+Mg) ratios. Clinopyroxenes have lower TiO_2 and Al_2O_3. These chemical features indicate that orthopyroxenes and clinopyroxenes in the rocks have metamorphic genetics. Biolites and some amphiboles are Ti-enriched, replying products formed under high-T metamorphic conditions, and even granulite-facies conditions. Based on mineral paragenesis, mineral generation and mineral geothermobaromemter. the P-T conditions of peak and retrograde metamorphism of the AMG are 750～780℃, 0.6～0.7 GPa and 590～620℃, 0.23～0.37 GPa, respectively, and the former one implies the crustal depth of ca. 20～25km. The discovery of the AMG has an important significance on further study of formation and structure of deeper crust in the Altay area and continental geodynamic mechanism in North Xinjiang, China and even Central Asia.